Phytochemical standardization, antioxidant, and antibacterial evaluations of Leea macrophylla: A wild edible plant - Joshi A.; Prasad S.K.; Joshi V.K.; Hemalatha S. (My University, 2025)
In Ayurveda, Leea macrophylla Roxb. ex Hornem. (Leeaceae) is indicated in worm infestation, dermatopathies, wounds, inflammation, and in symptoms of diabetes. The present study aims to determine the antioxidant and antibacterial potential of ethanolic extract and its different fractions of Leea macrophylla root tubers using phytochemical profiling which is still unexplored. Quantitative estimations of different phytoconstituents along with characterization of ethanol extract using high performance liquid chromatography (HPLC) were performed using chlorogenic acid as a marker compound for the first time. The extract and its successive fractions were also evaluated for in vitro antioxidant activity using different models. The extract was further tested against a few Gram-positive and Gram-negative bacteria for its antibacterial activity. Phytochemical screening and quantitative estimations revealed the extract to be rich in alkaloid, flavonoid, phenols, and tannins, whereas chlorogenic acid quantified by HPLC in ethanol extract was 9.01% w/w. The results also indicated potential antioxidant and antibacterial activity, which was more prominent in the extract followed by its butanol fraction. Copyright © 2016, Food and Drug Administration, Taiwan. Published by Elsevier Taiwan LLC.